2013
DOI: 10.1038/ng.2799
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent inactivation of STAG2 in bladder cancer is not associated with aneuploidy

Abstract: Urothelial bladder cancer (UBC) is heterogeneous at the clinical, pathological, and genetic levels. Tumor invasiveness (T) and grade (G) are the main factors associated with outcome and determine patient management (1). A discovery exome sequencing screen (n=17), followed by a prevalence screen (n=60), identified new genes mutated in this tumor coding for proteins involved in chromatin modification (MLL2, ASXL2, BPTF), cell division (STAG2, SMC1A, SMC1B), and DNA repair (ATM, ERCC2, FANCA). STAG2, a subunit of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
206
4
8

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 237 publications
(235 citation statements)
references
References 35 publications
17
206
4
8
Order By: Relevance
“…Such trends will undoubtedly continue in the years to come. It will also be important to determine to what extent mutations or misregulation of cohesin and condensin subunits might contribute to human cancers (Ham et al 2007;Balbás-Martínez et al 2013;Guo et al 2013;Kon et al 2013;Solomon et al 2013). Third, and, finally, all issues described above need to be addressed, also, from an evolutionary point of view.…”
Section: Resultsmentioning
confidence: 99%
“…Such trends will undoubtedly continue in the years to come. It will also be important to determine to what extent mutations or misregulation of cohesin and condensin subunits might contribute to human cancers (Ham et al 2007;Balbás-Martínez et al 2013;Guo et al 2013;Kon et al 2013;Solomon et al 2013). Third, and, finally, all issues described above need to be addressed, also, from an evolutionary point of view.…”
Section: Resultsmentioning
confidence: 99%
“…Meanwhile, Balbás-Martínez et al (2013) suggested that knocking down STAG2 in bladder cancer cells did not increase aneuploidy. As seen by determining chromosome number, knocking down STAG2 in bladder cancer cells may affect the degree of aneuploidy, such as more monosomies, trisomies and so on, and result in little offset of chromosome peak to show a statistical difference.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, in myeloid neoplasms, recurrent mutations and deletions have been detected in another study (Kon et al, 2013). Although there is dispute concerning the mutation of STAG2 in other carcinomas, it is reported by many scientists that there is a frequent mutation of STAG2 in bladder cancer (Solomon et al, 2011(Solomon et al, , 2013Balbás-Martínez et al, 2013). However, there is currently no evidence that shows whether loss of STAG2 leads to aneuploidy in bladder cells.…”
Section: Introductionmentioning
confidence: 96%
“…Although TERT mutations are present in up to 79% of bladder neoplasms, they have no association with clinical outcome; however, its presence can be of great diagnostic utility, given the relative rarity of this mutation in other tumours that may have overlapping histology. Next-generation sequencing efforts have demonstrated that the mutational landscape of urothelial tumours are quite complex, with >300 mutations, >200 copy number alterations, and >20 rearrangements per tumour [108,[115][116][117]. Only lung cancer has been shown to harbour a higher rate of mutations, although most are certainly passenger mutations with no functional consequence [118].…”
Section: Genomics Of Urothelial Carcinomamentioning
confidence: 99%